KORELASI ANTARA BIMBINGAN BELAJAR DAN MOTIVASI DENGAN HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - U Fitri Melani; Hery Kresnadi; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find out the relationship between guidance and motivation withthe learning outcomes of students of grade V of Public Elementary School 15 SouthPontianak. The research method used is descriptive quantitative with a form ofcorrelation study research. The population in this study was students of grade V SDN15 South Pontianak. The samples in this study were determined using nonprobabiltysampling techniques with saturated sampling type of all students of grade V SDN 15Pontianak Selatan. The source of this research data is a list of the scale of the parentlearning guidance questionnaire and the motivation of learning students of grade VSDN 15 Pontianak Selatan as well as the document of the value of learning theme 6.The results showed the parents' learning guidance of 83.25% of students wasincluded in the excellent category, the motivation of learning of learners by 80.05%was included in the category very well, and the learning outcomes of 83.4% fall intothe category very well. The correlation between guidance and learning outcomesobtained results of 0.655 falls into the strong category. The correlation betweenmotivation and learning outcomes was 0.676 in the strong category. Correlationguidance and motivation of 0.708 fall into the strong category. The correlationbetween guidance and motivation with learning outcomes of 0.720 falls into thestrong category.Keywords: Parental Learning Guidance, Learning Motivation, LearningOutcomes